An Aggregated Comorbidity Measure Based on History of Filled Drug Prescriptions: Development and Evaluation in Two Separate Cohorts. Issue 4 (2nd April 2021) - Gedeborg, Rolf; Sund, Malin; Lambe, Mats; Plym, Anna; Fredriksson, Irma; Syrjä, Johan; Holmberg, Lars; Robinson, David; Stattin, Pär; Garmo, Hans
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The ability to account for comorbidity when estimating survival in a population diagnosed with cancer could be improved by using a drug comorbidity index based on filled drug prescriptions. Methods: We created a drug comorbidity index from age-stratified univariable associations between filled drug prescriptions and time to death in 326, 450 control males randomly selected from the general population to men with prostate cancer. We also evaluated the index in 272, 214 control females randomly selected from the general population to women with breast cancer. Results: The new drug comorbidity index predicted survival better than the Charlson Comorbidity Index (CCI) and a previously published prescription index during 11 years of follow-up. The concordance (C)-index for the new index was 0.73 in male and 0.76 in the female population, as compared with a C-index of 0.67 in men and 0.69 in women for the CCI. In men of age 75–84 years with CCI = 0, the median survival time was 7.1 years (95% confidence interval [CI] = 7.0, 7.3) in the highest index quartile. Comparing the highest to the lowest drug comorbidity index quartile resulted in a hazard ratio (HR) of 2.2 among men (95% CI = 2.1, 2.3) and 2.4 among women (95% CI = 2.3, 2.6). Conclusions: A new drug comorbidity index based on filled drug prescriptions improved prediction of survival beyond age and the CCI alone. The index will allow a more accurate baseline estimation of expected survival for comparing treatment outcomes and evaluating treatment guidelines in populations of people with cancer.